PRELIMINARY STUDY ON THE USE OF INHIBIN TO IMPROVE THE WATER BUFFALO SUPEROVULATION - Guang-Sheng Qin; Ying-ming Wei; Qin-yang Jiang; Yong-Chang Qin; De-ru Li; Al-Kal Abakar; Bin Pan; Bao- Jian Chen; Xian-bao Mao; Zhen-dan Shi; He-sheng Jiang (Journal of Animal and Plant Sciences, 2012)
Seventeen female buffaloes with normal estrus cycle were randomly divided into 10 heads for the experimental group and 7 heads for the control. In the experimental group 1mg/head of the Recombinant porcine inhibin  subunit fusion protein was administrated as the first immunization. After 28 and 56 days, the immunization was strengthened by the dose of 0.5 mg/head. At the same time, an adjuvant consisting to the mixture of mineral oil and physiological saline was administrated to the control group. In both the experimental group and the control, at the days 28 (first strengthened immunization) and 56 (second strengthened immunization), the follicles size and number were monitored and counted respectively by B-mode linear array ultrasound scanner .At eight days after the super ovulation the follicles and corpus luteum count were performed by B-mode linear array ultrasound scanner and palpation. The results showed that, in the experimental group compared with the control one the average follicles number enhanced (from 8.8 to 15.0) after strengthening the immunization, but the difference was not significant (P＞0.05). After the super ovulation, in the experimental group the mean number of the follicles and corpus luteum and ovulation rate were 12.2±0.79, 9.0±1.06 and 73.77 % respectively, compared to the control, the difference was significant (P＜0.05). There was no difference between the total embryo recovery number and available embryo number. These results demonstrated that the reimmunization of inhibin can be used to enhance ovarian follicular development and ovulation rate and it is suitable to superovulation in buffaloes.
Keywords: water buffalo; inhibin immunization; follicle development; super ovulation